Pengaruh Kompetensi Manaj Erial Kepala Sekolah Dalam Meningkatkan Mutu Dan Kinerja Guru : SMP Darul Ulum 1 Peterongan - Septian Ragil Anandita; Zaidatur Rizkiyah; Khotim Fadhli; Wisnu Mahendri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Management is important in all areas of life. With management, an organization's performance can run optimally. Likewise with educational institutions. With good management, an educational institution will be able to develop optimally as expected. In the world of education, the quality of school management will depend on a school principal who plays the role of manager and as a manager, the school principal has a big responsibility in managing, coordinating, mobilizing and harmonizing all educational resources in his school. This is where the essence is that the principal must be able to carry out the role of principal and have abilities in the field of school management. The principal is the administrator who holds the key to improving the progress of the school.